Philosophy of plant cognition interdisciplinary perspectives - Ferretti, Gabriele; Schulte, Peter 1977-; Wild, Markus 1971- (Routledge, 2025)
"This volume features new research about the philosophy of plant intelligence and plant cognition, one of the most intriguing and complex current debates at the intersection of biology, cognitive science and philosophy. The debate about plant cognition is marked by deep disagreements. Some theorists are confident that the empirical evidence supports the ascription of cognitive capacities to plants. Others hold that such claims are overblown, and defend more traditional, non-cognitive accounts of plant behavior. Still others seek to formulate intermediate positions. This volume brings together leading researchers from across this theoretical spectrum to tackle the foundational questions that are at issue in the debate about plant cognition. The contributions focus on the philosophical questions raised by recent discoveries and controversies in the empirical sciences, such as: Can plants be said to have genuine cognitive abilities? Can they be characterized as representing or perceiving their environment, as pursuing goals, or even as having some form of conscious experience? Which data could provide evidence for such characterizations? And what are possible implications of these issues for general questions about the nature of cognition, representation, perception, and consciousness? Philosophy of Plant Cognition will be of interest to scholars and students working in philosophy of mind, philosophy of biology, cognitive science, and plant biology"--
Keywords: Intelligenz; Pflanzen; Kognition; Philosophie; Plant physiology; Plants (Philosophy); Plant ecophysiology; Philosophy of mind; Physiologie végétale; Plantes (Philosophie); Plantes / Écophysiologie; Philosophie de l'esprit; Aufsatzsammlung